NCKAP1 is a Prognostic Biomarker for Inhibition of Cell Growth in Clear Cell Renal Cell Carcinoma - Chen, Jiasheng; Ge, Jianzhang; Zhang, Wancong; Xie, Xuqi; Zhong, Xiaoping; Tang, Shijie (Frontiers in Genetics, 2022)
Background: Clear cell renal cell carcinoma (ccRCC) is the most frequent type of kidney cancer. Nck-associated protein 1 (NCKAP1) is associated with poor prognosis and tumor progression in several cancer types, but the function and prognostic value of NCKAP1 in ccRCC remain poorly understood. Methods: Using the Ualcan database, we evaluated the correlation between NCKAP1 expression and clinical features of ccRCC. These data were validated by immunohistochemical staining for NCKAP1 in a cohort of ccRCC patients. We assessed the prognostic value of NCKAP1 using GEPIA2 survival analysis. NCKAP1 function was characterized in vitro and in vivo using NCKAP1-overexpression ACHN cell lines. The LinkedOmics and GSCALite databases were used to investigate identify potential NCKAP1-targeted medicines that may play a role in the treatment of ccRCC. The impact of NCKAP1 expression on immune infiltration was also evaluated. Results: NCKAP1 was significantly downregulated in ccRCC and correlated with advanced clinicopathological features and poor prognosis. Overexpression of NCKAP1 in ACHN cells reduced proliferation, invasion and migration capacity in vitro and inhibited tumor growth in vivo. According to the LinkedOmics, GSCALite and TIMER databases, NCKAP1 and related genes function primarily in ribosomal signaling, oxidative phosphorylation, TGF-β, and EMT-related signaling pathways. NCKAP1 was also shown to positively correlate with immune cell types, biomarkers, and immune checkpoints in ccRCCs. Conclusions: NCKAP1 may play a vital tumor-suppressive role in ccRCC and is potentially a useful prognostic biomarker.